Evaluation of two automated cell counters for the analysis of hematopoietic progenitor cell apheresis products. (26th April 2017) - Gils, S.; Cauwelier, B.; Devos, H.; Vanlaere, I.; Roggeman, S.; Emmerechts, J.
Summary: Introduction: Routine hematology parameters in hematopoietic progenitor cell apheresis products (HPC‐A) are usually determined using automated cell counters. These instruments, however, are designed to analyze whole blood samples, that differ considerably from HPC‐A in blood cell composition. This study evaluates the performance of two automated cell counters for the analysis of HPC‐A. Methods: Routine hematology parameters [red blood cells (RBC), hematocrit (HCT), mean corpuscular volume (MCV), white blood cells (WBC), WBC differentiation, and platelets (PLT)] were determined on the Unicel DxH 800 instrument (Beckman Coulter) and the XN‐350 instrument (Sysmex). Correlations with the reference methods, intrarun precision, and linearity of the analyses were studied. Results: Good correlations were found for almost all parameters. However, RBC count was overestimated by XN‐350, using the impedance technique, as was neutrophil percentage using DxH 800. Coefficients of variation for intrarun precision were below 10% on both analyzers for all parameters, except for neutrophil percentage (14.7%) and PLT (10%) on DxH 800. Both instruments showed good linearity for all parameters, except for RBC and HCT on DxH 800. Conclusion: With the exception of the measurement of neutrophils on DxH 800 and RBC by the impedance technique on the XN‐350, routine hematology parameters in HPC‐A can safely be determined using automated cell counters.